Corpus-based analysis of shifts in China’s diplomatic stance across seven decades (1949–2018) - Tian, Xujun; Li, Xiaoqian (Frontiers in Psychology, 2022)
This study investigates the changes in China’s diplomacy in the past seven decades based on the diachronic corpus of Chinese diplomatic discourse from 1949 to 2018 using corpus based critical discourse analysis theoretical insights. The study examines the targeted keywords used in the seven periods of Chinese diplomatic discourse and their significant collocations. The results show that China has worked with the United States, Japan, the United Kingdom, and some Asian, Latin American, and African countries to safeguard world peace while opposing war, establish good relations with these countries, and promote mutual development through cooperation. In addition, China’s diplomacy has experienced politics-oriented and economy-oriented eras and is now in an era of global sustainable development. Therefore, Chinese diplomatic discourse is the linguistic representation of China’s diplomacy, fundamentally determined by its national interests and changing social and historical situations domestically and internationally.